MAXIMUM POWER POINT TRACKING (MPPT) PADA SOLAR PANEL - Liana, Valencia; Ardhita, Maya (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Electrical energy is a major necessity in human life today, being the driving force for various activities that are increasing. Renewable energy sources are alternative energy sources available around us, namely sunlight, which can be converted into electrical energy through solar panels. However, because solar panels have non-linear characteristics, causing the output power of solar panels to vary so that a maximum power point tracking (MPPT) algorithm is needed. The methods used are the temperature method and the PO (Perturb & Observe) method. The test results when there is an increase in light intensity, it will affect the increase in voltage and current produced by the solar panel output. And vice versa, if there is a decrease in light intensity, there is also a decrease in the voltage and current produced. The intensity of light entering and absorbed by the solar panel will change every time, from duty cucle 0 to 255. The lowest light intensity, 91, does not produce any voltage and current, while the highest light intensity, 238, produces a voltage of 6.06 V and a current of 128 mA.